CYBER CRIME AWARENESS: INTERNET KNOWLEDGE DAN E-COMMERCE USE PADA UMKM DI KABUPATEN BANTUL YOGYAKARTA - Tri Siwi Nugrahani; Faizal Ardiyanto; Sulkhanul Umam (MANAJEMEN DEWANTARA, 2019)
This research aimed to test the effect of internet knowledge and e-commerce use both partially and simultaneously using multiple linear regression analysis. Convenience sampling is used in this research where 59 SMEs from Bantul, Special Region of Yogyakarta Province are involved. The result of this research prove that all the hypotheses are supported except for first hypotheses which stated that internet knowledge significantly and positively affects cybercrime awareness. Therefore, e-commerce use is significantly and positively affects cybercrime awareness, and also internet knowledge and e-commerce is simultaneously affects cybercrime awareness.Keywords: e-commerce, cybercrime, awareness, SMEs, internet knowledge